PENGARUH BIAYA BAHAN BAKU TERHADAP VOLUME PRODUKSI PADA PT. SUBUR MEKAR ABADI PONDOK BATU KABUPATEN TAPANULI TENGAH - Nur Asilah; Sahat Simatupang; Sriayu Aritha Panggabean (Universitas Sains dan Teknologi Komputer, 2022)
Companies engaged in manufacturing carry out routine production activities to produce goods. Production activities start from purchasing materials, paying labor wages to process these materials and incurring the necessary costs so that these materials can be converted into finished products that are ready to be sold for profit. Therefore, the standard cost is the planned cost for a product based on current business conditions. Costs of materials and labor are usually based on normal or current conditions taking into account possible changes in price levels and tariffs. So for the purpose of production cost efficiency in this study can be used standard costs. Raw material costs are the costs that you need to spend to get raw materials to produce goods, including operational costs, transportation costs, storage costs, and so on, and production volume is the number of commodities and services that are actually produced from the production process carried out. by the industrial companies themselves within a certain period of time. This type of research uses associative research, which aims to determine the effect of raw material costs on production volume at PT. Subur Mekar Abadi, the sample for this research is financial data for 2019-2021. The results of partial testing of the raw material cost variable (X) on the production volume variable (Y) show that the value of t count > t table is 3.181 > 2.353, which means Ha is accepted and Ho is rejected, it can be concluded that raw material costs affect production volume